133 A randomised controlled trial of catheter ablation of atrial fibrillation comparing manual and robotic navigation: experience with the hansen robotic system. (22nd September 2015) - Duncan, E; Liew, R; Goromonzi, F; Richmond, L; Baker, V; Thomas, G; Tayebjee, M; Finlay, M; Abrams, D; Dhinoja, M; Earley, M; Sporton, S; et al.
Abstract : Introduction: Catheter ablation of atrial fibrillation (AF) is technically challenging. Robotic catheter ablation with the Hansen Sensei system aims to improve outcome through improved tissue contact and catheter stability while reducing fluoroscopy and operator fatigue. We present data from the first randomised controlled trial comprising patients with both paroxysmal and persistent AF. Method: Patients undergoing first time AF ablation were randomised to robotic or manual catheter ablation. Using a 3D mapping system (St Jude NavX), all patients underwent wide area circumferential ablation (WACA). For persistent AF further lesions were delivered (roof line, CS lines, complex fractionated electrograms). Patients underwent clinic review at 3 months with assessment of symptoms and 12 lead ECG. Data are presented as mean±SD. p<0.05 is significant. Results: Hundred patients (mean age 57±10) with AF were randomised. Total procedure times were not prolonged with the robotic approach in either paroxysmal (PAF) or persistent (PERS) AF (PAF: Robot 247±64 and Manual 218±66 min; p=0.2; PERS AF: Robot 328±66 and Manual 315±80 min; p=0.4). Total fluoroscopy time was lower with robotic ablation in persistent AF cases but not PAF (PAF: Robot 49±26 and Manual 49±26 min; p=0.75; PERS AF: Robot 53±22 and Manual 81±30 min; p<0.01). Comparable rates of pulmonary vein isolation were achieved (96% and 98%; p=NS), and rates of PV re-connection at the end of the case were also similar (22.2% and 23.0%, p=NS). The ablation catheter tip dislodged less frequently during robotic cases (2.0±1.9 and 8.9±7; p<0.0001) suggesting improved stability. However, a trend was noted that suggests fewer patients with persistent AF may be ablated to sinus rhythm with the robot (22% vs 48%; p=0.07). Major complication rates were 8.8% (one death, two tamponades, one retroperitoneal bleed) for robotic ablation and 4.2% (one tamponade, one CVA) for manual (p=NS), possibly reflecting a learning curve when using the robotic approach. At 3 month follow-up no significant difference was seen between groups in the following parameters: (1) symptom improvement (PAF: Robot 84% and Manual 86%; p=NS; PERS AF: Robot 71% and Manual 74%; p=NS) (2) anti-arrhythmic drug use (PAF: Robot 20% and Manual 26%; p=NS; PERS AF: Robot 35% and Manual 35%; p=NS) (3) 90 day procedural success as defined by sinus rhythm at follow up, with no documented atrial arrhythmias and no symptoms suggestive of continuing arrhythmia (PAF: Robot 80% and Manual 71%; p=NS; PERS AF: Robot 48% and Manual 65%; p=NS). Conclusions: Acute procedural success and 3 month outcome following AF ablation using Robotic catheter navigation are equivalent to those achieved with manual. Fluoroscopy times are reduced in persistent AF cases.